Comparative Study Of The Quality Of Rasomalai Manufactured From Cow And Buffalo Milk - Sayedatunnesha, M; Wadud, A; Islam, MN; Islam, MA; Hossain, MA (Bangladesh Journal of Animal Science, 2012)
The experiment was conducted to compare the quality of rasomalai manufactured from cow milk and buffalo milk, two types of rasomalai were prepared named as- A (cow milk) and B (buffalo milk). The qualities of prepared rasomalai were evaluated physically, chemically and microbiologically. It was found that flavor, body and texture, color and appearance and total score of A and B type samples differed significantly (P<0.01) and taste score non-significantly (P>0.05). The total solids, protein, fat, ash and carbohydrate content of A and B were 461.10±6.45 and 540.17±3.77; 61.67±1.20 and 84.00±1.15; 75.33±3.18 and 125.67±3.48; 9.13±0.09 and 12.50±0.12 and 314.97±4.53 and 318.00±1.53 g/kg, respectively. All of them varied significantly (P<0.01) except carbohydrate (P>0.05). The acidity of α and β were 0.21±0.00 and 0.19±0.003 per cent, respectively and showed significant difference (P<0.01). Total viable count of A and B type samples were non-significantly (P>0.05) different and the values were 3.84±0.05 and 3.77±0.07 log cfu/g. The Coliform was absent both in A and B type sample. Buffalo milk rasomalai earns extra profit of Tk. 35/kg than the cow milk rasomalai. Physical examination revealed that type A was better than type B but the chemical and microbiological findings and also the pricing of rasomalai showed that buffalo milk rasomalai was superior to cow milk rasomalai. DOI: http://dx.doi.org/10.3329/bjas.v37i1.9869 BJAS 2008; 37(1): 57-62